“We Combined the Old Culture with Modern Civilization”: Cultural Motion in the Local Museum in Horodnic de Jos, Romania - Klimaszewski, Cheryl (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2016)
This poster investigates temporality in a local museum in Horodnic de Jos, Romania. Greg Urban’s work on cultural motion provides theoretical foundation for mapping constructions of past and future within the museum site, revealing zones of proximity. Museummaking activities take place across these zones, creating new connections between past and future. Cette affiche étudie la temporalité dans un musée local à Horodnic de Jos, en Roumanie. Les travaux de Greg Urban sur le mouvement culturel fournissent le fondement théorique pour les constructions établissant les correspondances entre passé et avenir dans le site du musée, révélant des zones de proximité. Les activités muséographiques ont lieu dans ces zones, où elles créent de nouveaux liens entre le passé et l’avenir.